Prevalence of drug injection, sexual activity, tattooing, and piercing among prison inmates - Moazen, Babak; Saeedi Moghaddam, Sahar; Silbernagl, Marisa A.; Lotfizadeh, Masoud; Bosworth, Rebecca J.; Alammehrjerdi, Zahra; Kinner, Stuart A.; Wirtz, Andrea L.; Bärnighausen, Till; Stöver, Heino J.; Dolan, Kate A. (Epidemiologic reviews, 2018)
Prisoners engage in a range of risk behaviors that can lead to the transmission of viral infections, such as HIV, hepatitis B and hepatitis C. In this review, we summarize the epidemiologic literature from 2007 to 2017 on 4 key risk behaviors for human immunodeficiency virus and hepatitis C virus among prisoners globally: drug injection, sexual activity, tattooing, and piercing. Of 9,303 peer-reviewed and 4,150 gray literature publications, 140 and 14, respectively, met inclusion criteria covering 53 countries (28%). Regions with high levels of injection drug use were Asia Pacific (20.2%), Eastern Europe and Central Asia (17.3%), and Latin America and the Caribbean (11.3%), although the confidence interval for Latin America was high. Low levels of injection drug use in prison were found in African regions. The highest levels of sexual activity in prison were in Europe and North America (12.1%) and West and Central Africa (13.6%); low levels were reported from the Middle East and North African regions (1.5%). High levels of tattooing were reported from Europe and North America (14.7%), Asia Pacific (21.4%), and Latin America (45.4%). Prisons are burdened with a high prevalence of infectious diseases and risk behaviors for transmission of these diseases, and, commonly, a striking lack of evidence-based infection control measures, even when such measures are available in the surrounding community. Given that most prisoners return to these communities, failure to implement effective responses has repercussions not only prisoner health but also for public health.